Development of coordination abilities of fencers aged 10-12 years living in the territory of martial law - Iryna Kryventsova; Vladimir Potop; Krzystzof Prusik; Dmytro Samoilov (Pedagogy of Health)
Background and purpose. Success in sports activities is determined by various criteria, among which the level of development of coordination abilities stands out. The initial stage of training young athletes is important for the development of coordination abilities. At the same time, the martial law in the territory of residence of the athletes entails the need to ensure the safety conditions of life. Forced relocation of young athletes to safer places of residence presents coaches and parents with other training conditions. The purpose of the research is to identify opportunities for the development of special coordination abilities of young fencers aged 10-12 years in crisis situations caused by martial law.